Landscape Fragmentation and Non-breeding Greater Sage-Grouse - Jay F. Shepherd; Kerry P. Reese; John W. Connelly (Ecology, Conservation, and Management of Grouse, 2011)
Greater Sage-Grouse (Centrocercus urophasianus), a shrubsteppe obligate species, evolved within an environment subject to disturbances that occasionally revert sagebrush communities to early successional stages. Wildfire is the primary natural disturbance event determining the spatial and temporal distribution of successional stages, as well as the plant community composition, in the sagebrush shrubsteppe ecosystem (Harniss and Murray 1973, Young and Evans 1978, Humphrey 1984, Akinsoji 1988, Whisenant 1990). Prior to European settlement, Greater Sage-Grouse habitat was characterized by large areas of sagebrush cover with relatively isolated areas in earlier seral stages due to wildfire. Currently, sagebrush shrubsteppe communities can be subject to